Factorial analysis of biological treatment for contaminated wastewater from hatchery industry - Norazwina, Zainol; Che Asilah Ilyana, Che Jazlan (IOP Publishing, 2020)
The wastewater from a hatchery was dissimilar from a production farm in terms of quality and quantity of waste. The sources of wastewater were basically from uneaten food and fish feces. Biological treatment was a very promising process for removing dissolved organics from refinery wastewater. However, the low availability of clean water has become critical issue to the shrimp grower. Further, carbon and phosphorus are the main constituents of most wastes, and removal of such elements from waste effluents can reduce environmental stress and minimize ecosystem deterioration. The purpose of this study is to evaluate the factors affecting the removal of chemical oxygen demand (COD) and total phosphorus (TP) in the contaminated wastewater from hatchery industry. The factors were: ratio acclimatized mixed culture (AMC) to synthetic wastewater (SW) (1:3 and 2:3), the presence and absent of support media (Yes and No), agitation (0 rpm and 100 rpm) and retention time (4 days and 8 days). The responses were COD and TP removal. Design Expert software was used to construct experimental design where all the factor was randomized. As a results, ratio AMC to the SW, agitation and retention time were the most contributing factors to all the responses. The best conditions for the contaminated wastewater from hatchery industry was at ratio (1:3) AMC:SW, present of support media, 0 rpm agitation and 4 days retention time. At this condition the removal for COD and TP were 26.5% and 42.9% respectively. However, by separating the best condition for COD and TP, the removal can achieved 74.6% and 75.7% respectively. It can be concluded that the biological treatment using AMC can treat contaminated wastewater from hatchery industry.